Biofertilizer based on fish waste increases the yield of Vigna unguiculata L. Walp, Zea mays L., and the rhizospheric microbiota - Maquen-Perleche, José (2023)
Crops of Vigna unguiculata L. “cowpea” and Zea mays L. “corn” require chemical fertilizers for proper growth and development; however, its inadequate application contaminates the environment, creating the need to search new alternatives that reduce its impact. Due to this, the objective of this research was to determine the effect of a biofertilizer from fish wastes on the yield of cowpea and corn, and its effect on their rhizospheric microbiota. The physicochemical and biological characteristics of the biofertilizer were determined, and then was applied on the field under a completely randomized block design with six treatments: absolute control, chemical control, biofertilizer at 1%, 1.25%, 1.5% and 1.25% plus chemical fertilizer. The application of biofertilizer at 1, 1.25 and 1.5% increased the height, root length and yield of cowpea; however, the increase percentages were lower than those obtained with chemical fertilizer and the biofertilizer at 1.25% plus chemical fertilizer. In the case of corn, all treatments with biofertilizer increased the growth and yield of aerial biomass compared to the control, and the percentages of increase exceeded the chemical fertilizer in terms of the number of leaves, length and root biomass. In addition, the biofertilizer increased the microbial fertility of the soil expressed as the number of colony-forming units of nitrogen-fixing and phosphate-solubilizing microorganisms per gram of soil in both crops. In conclusion, a positive effect of the biofertilizer from fish wastes was evidenced, which increased the yield of cowpea and corn, as well as an increase in soil microbial fertility.